Analysis of the Correlation between Morphological Characteristicsand Reducibility of Displaced Articular Disc in Saudi Population (Bangladesh Journal of Medical Science, 2026)
The objective of this study was to identify the most common patterns of articular disc displacement directions and the associated morphological alterations of the TMJ meniscus in the Saudi population that had MRI examinations for TMJ dysfunction. A total of 61 MRI scans of temporomandibular disorders (TMDs) patients were selected for this retrospective study. The patients were imaged using Proton Density (PD) weighted MRI, the imaging protocol consists of oblique sagittal images (closed and open mouth) and oblique coronal images (closed mouth). The DICOM (Digital Imaging and Communication in Medicine) files of each MRI scan were exported and evaluated. There were 42 (34.4%) TMJs that did not have articular disc displacement (ADD). However, 80 (65.6%) TMJs reveal ADD in different directions with the anteromedial disc displacement was the most common direction of displacement (32%). There is a significant relationship between the existence of reduction and Articular disk (AD) morphology, that ADD without reduction has much lower frequency of normal right TMJ than those with reduction (χ2 = 12.246, p =0.002. This is also valid for left TMJ (χ2 = 19.950, p < 0.001). MRI samples investigated revealed that the articular disc morphology may influence the reduction ability of the displaced articular disc.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S297-S304